2005
DOI: 10.1182/blood.v106.11.1814.1814
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Graft Versus Host Disease (cGVHD) Following Unrelated Donor Hematopoietic Stem Cell Transplantation (HSCT): Higher Response Rate in Recipients of Unrelated Donor (URD) Umbilical Cord Blood (UCB).

Abstract: The nature of chronic graft versus host disease (cGVHD) after umbilical cord blood (UCB) transplant has not been well characterized. We analyzed clinical presentation and response to treatment in 170 patients with cGVHD (123 following transplant from an unrelated donor (URD) and 47 following transplant from UCB). URD transplant recipients were significantly younger (median age 25 (0.5–57) versus 39 (0.2–61) years, p = 0.002; and were less likely to receive a transplant from an HLA mismatched donor (33% versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…So higher degrees of HLA mismatches between UCB and patients have been proved to be better tolerated by means of a reduced risk for lethal GVHD, lower incidences of cGVHD, and more treatment responsive GVHD. Hwang et al reported a meta-analysis of studies of UCB and URD in pediatric AML and found that the incidence of cGVHD was lower with UCBT, but the incidence of grade III-IV aGVHD did not differ (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…So higher degrees of HLA mismatches between UCB and patients have been proved to be better tolerated by means of a reduced risk for lethal GVHD, lower incidences of cGVHD, and more treatment responsive GVHD. Hwang et al reported a meta-analysis of studies of UCB and URD in pediatric AML and found that the incidence of cGVHD was lower with UCBT, but the incidence of grade III-IV aGVHD did not differ (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research over recent years has established the safety and efficacy of UBCT in children with a variety of malignant and nonmalignant diseases. 6,15,16 UBCT presents the following advantages: a lower incidence and lower severity of GVHD, 17,18 in patients with leukemia 20,21 showed that the median duration to neutrophil and platelet engraftment was 23-27 and 38-60 days, respectively. Other studies 3,15,25 showed that UCBT was effective in children with non-malignant diseases, in whom the median duration to neutrophil and platelet recovery was 22-25 and 40-87 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the malignant disease group, three patients who received UCB died before engraftment. The median duration to neutrophil and platelet engraftment was 16 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and 35 (6-107) days, respectively ( The median duration to neutrophil engraftment and platelet engraftment was similar between the two groups (P = .986, P = .133).…”
Section: Hematopoietic Recovery and Engraftmentmentioning
confidence: 99%
“…A total of 34 patients underwent ECP for steroid-refractory aGVHD from June 2001 to September 2013. A median of 11 ECP procedures per patient were performed (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median follow-up for surviving patients was 4 years (range, 2 months-12 years), while it was 7 months for deceased patients (range, 35 days-11 months).…”
Section: Agvhd Patientsmentioning
confidence: 99%
“…7,8 Furthermore, despite better donor selection, GVHD prophylaxis, and treatment, chronic GVHD (cGVHD) affects 50% of long-term transplant survivors and is lethal in 20% to 40% of affected patients. 9 Primary therapy for extensive cGVHD usually includes steroids and calcineurin inhibitors, [10][11][12][13][14][15][16][17][18] but the probability of cGVHD response is highly variable. [19][20][21][22][23] Extracorporeal photopheresis (ECP) was introduced nearly 30 years ago to treat cutaneous T-cell lymphoma and autoimmune diseases, such as scleroderma.…”
mentioning
confidence: 99%